2022
DOI: 10.51821/85.4.10634
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the side effects of antivirals in chronic hepatitis B patients: a single-center experience

Abstract: Background and study aim: Entecavir (ETV), Tenofovir Disoproxil Fumarate (TDF), and Tenofovir Alafenamide (TAF) have been approved for treating Chronic Hepatitis B (CHB) and recommended due to their high safety profile and high resistance barriers. This study aimed to evaluate the kidney functions, bone, and metabolic parameters in CHB patients receiving ETV, TDF, and TAF treatment. Patients and methods: In this retrospective cohort study, a total of 469 CHB patients who were treated with TDF (n = 256), ETV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies have shown that long-term use of antiviral drugs can lead to bone and kidney damage. [10][11][12][13][14][15] Many studies have shown that nucleoside analogues have renal toxicity, mainly because nucleoside analogues are affected by renal metabolism, mainly proximal renal tubules, which can lead to a decrease in eGFR. In addition, reduced phosphate reabsorption by proximal renal tubules causes bone disease, with the main outcome being hypopuricemia, hypophosphatemia leading to defects in bone mineralization, osteomalacia, and fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that long-term use of antiviral drugs can lead to bone and kidney damage. [10][11][12][13][14][15] Many studies have shown that nucleoside analogues have renal toxicity, mainly because nucleoside analogues are affected by renal metabolism, mainly proximal renal tubules, which can lead to a decrease in eGFR. In addition, reduced phosphate reabsorption by proximal renal tubules causes bone disease, with the main outcome being hypopuricemia, hypophosphatemia leading to defects in bone mineralization, osteomalacia, and fractures.…”
Section: Introductionmentioning
confidence: 99%